Vitamin D status in sarcoidosis: a cross-sectional study - Papanikolaou, Ilias C; Tabila, Brian; Tabila, Kristina; Borok, Zea; Sharma, Om P; Gould, Michael K (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Hypercalcemia, a common feature in sarcoidosis, is due to the excessive production of active Vitamin D metabolite, 1,25(OH)2D. Levels of 25(OH) Vitamin D however may not be appropriate. Objectives: To assess Vitamin D status and its clinical associations in sarcoidosis patients compared to a general respiratory diseases out-patient clinic population, serving as controls. Methods: 64 sarcoidosis cases and 53 control cases with other than sarcoidosis respiratory diseases, matched for age and sex were included in the study. Serum 25(OH)D, 1,25(OH)2D, calcium, angiotensin converting enzyme (ACE) were measured. 25(OH) Vitamin D was described as deficient when